2021
DOI: 10.1186/s13075-021-02488-w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sprifermin injection for knee osteoarthritis treatment: a meta-analysis

Abstract: Objective To perform a meta-analysis comparing the structural progression and clinical symptom outcomes as well as adverse events experienced from intra-articular injections of sprifermin compared to a placebo treatment for patients with knee osteoarthritis (KOA). Method We systematically searched the literature for studies that compared long-term outcomes between sprifermin and placebo injections for KOA treatment. Meta-analysis was performed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“… 120 A recent meta-analysis pooling data from eight reports of three original trials confirmed its disease-modifying properties such as improvement in cartilage thickness, volume and morphology. 153 However, it failed to exhibit symptomatic improvement measured by WOMAC subscores. As a note, structure-protective effects may prevent or delay KOA patients from reaching levels of debilitating pain in the long term despite lack of initial symptomatic improvement.…”
Section: Investigational Dmoad Agents Already In Phase II and Iii Tri...mentioning
confidence: 99%
“… 120 A recent meta-analysis pooling data from eight reports of three original trials confirmed its disease-modifying properties such as improvement in cartilage thickness, volume and morphology. 153 However, it failed to exhibit symptomatic improvement measured by WOMAC subscores. As a note, structure-protective effects may prevent or delay KOA patients from reaching levels of debilitating pain in the long term despite lack of initial symptomatic improvement.…”
Section: Investigational Dmoad Agents Already In Phase II and Iii Tri...mentioning
confidence: 99%
“…One of them represents a phase II multicenter randomized dose-finding clinical study [121]; clinicaltrials.gov NCT01919164), investigating the intra-articular administration of sprifermin. A meta-analysis of the efficacy and safety of sprifermin injection for knee OA treatment has been published very recently [122]. In parallel, a large number of other cytokine/growth factor therapies are in different phases of clinical trials and it will be interesting to see if any of these treatments will be effective in OA therapy [123,124].…”
Section: Cytokines In Oamentioning
confidence: 99%
“…Sprifermin has exhibited outstanding prospects in promoting cartilage repair, and intraarticular application of Sprifermin is safe and reliable ( Zeng et al, 2021 ). A comprehensive assessment of the specific role of Sprifermin in promoting cartilage repair and the evaluation of its potential molecular mechanisms are conducive to further improvement of Sprifermin.…”
Section: Basic Structure and Function Of Spriferminmentioning
confidence: 99%
“…In summary, clinical trials, in vitro experiments and animal experiments all indicate that Sprifermin possesses powerful performance in boosting chondrocyte proliferation and cartilage repair. Sprifermin has exhibited outstanding prospects in promoting cartilage repair, and intraarticular application of Sprifermin is safe and reliable (Zeng et al, 2021). A comprehensive assessment of the specific role of Sprifermin in promoting cartilage repair and the evaluation of its potential molecular mechanisms are conducive to further improvement of Sprifermin.…”
Section: Basic Structure and Function Of Spriferminmentioning
confidence: 99%
See 1 more Smart Citation